What defines a great surgeon? A survey study confronting perspectives - Luscan, Romain; Malheiro, Emeline; Sisso, Fiona; Wartelle, Sébastien; Parc, Yann; Fauroux, Brigitte; Bégué, Thierry; Johanet, Hubert; Denoyelle, Françoise; Garabédian, Erea-Noël; Simon, François (Frontiers in Medicine, 2023)
Background: The definition a great surgeon is usually reported by surgeons themselves. The objective of the study was to define a multi-faceted definition of a great surgeon, by confronting patients’, healthcare workers’ and surgeons’ perspectives. Study Design: An online open-ended questionnaire was created to identify 3 qualities and 3 shortcomings defining a great surgeon. Age, gender and profession of respondents were collected. Responses with a similar meaning were combined into word-groups and labelled within four themes: human qualities, Technical Surgical Skills (TSS), Non-Technical Skills (NTS) and knowledge. Multivariate analyses were conducted between themes and respondent characteristics. Results: Four thousand seven hundred and sixty qualities and 4374 shortcomings were obtained from 1620 respondents including 385 surgeons, 291 patients, 565 operating theatre (OT) health professionals and 379 non-OT health professionals. The main three qualities were dexterity (54% of respondents), meticulousness (18%) and empathy (18%). There was no significant difference between professional categories for TSS. Compared to surgeons, non-OT health professionals and patients put more emphasis on human qualities (29% vs 39% and 42% respectively, p<0.001). OT health professionals referred more to NTS than surgeons (35% vs 22%, p<0.001). Knowledge was more important for surgeons (19%) than for all other professional categories (p<0.001). Conclusions: This survey illustrates the multi-faceted definition of a great surgeon. Even if dexterity is a major quality, human qualities are of paramount importance. Knowledge seems to be underestimated by non-surgeons, although it essential to understand the disease and preparing the patient and OT team for the procedure.